Further Studies on Arcanobacterium phocisimile: a Novel Species of Genus Arcanobacterium. (6th February 2014) - Sammra, Osama; Balbutskaya, Anna; Hijazin, Muaz; Nagib, Samy; Alber, Jörg; Lämmler, Christoph; Abdulmawjood, Amir; Prenger-Berninghoff, Ellen; Timke, Markus; Kostrzewa, Markus; Siebert, Ursula
Abstract : Arcanobacterium phocisimile, a newly described species with the type strain A. phocisimile 2698 T isolated from a vaginal swab of a harbour seal and four additional A. phocisimile strains also isolated from four harbour seals could reliably be identified by phenotypic properties, by matrix assisted laser desorption ionization time of flight mass spectrometry (MALDI-TOF MS), and by sequencing the genomic targets 16S rDNA and 16S-23S rDNA intergenic spacer region and the genes rpoB and gap . The A. phocisimile strains investigated in the present study were isolated together with several other bacterial species indicating that the pathogenic importance of A. phocisimile remains unclear. However, the detection of peptidic spectra by MALDI-TOF MS and the presented phenotypic and genotypic approach might help to identify A. phocisimile in future.